Incomplete Milking in Early Lactation Does Not Affect Dairy Cows Resting Behaviors: Results from a Randomized Controlled Trial - Krug, Catarina; DeVries, Trevor J.; Roy, Jean-Philippe; Dubuc, Jocelyn; Dufour, Simon (Frontiers in Veterinary Science, 2017)
The objective of this study was to investigate the effect of incomplete milking during the first 5 d of lactation on the resting behavior of commercial dairy cows. The hypothesis was that the elevated intramammary pressure resulting from milk retained in the udder in incompletely milked cows could lead to a change in lying behaviour. This study was a randomized controlled trial in which cows from 2 farms were randomly allocated into a treatment (n = 18) or a control group (n = 14). Cows in the treatment group were milked incompletely (10 – 14 L / d) during the first 5 d of lactation, while cows in the control group were milked as usually done on farm. Resting behaviors were recorded with a data logger. Linear mixed models were used to quantify the effects of treatment group on three dependent variables measured between 2 and 14 days in milk: daily duration of lying time (h / d), lying bout frequency (bouts / d), and mean duration of lying bouts (min / bout). There was no significant effect of treatment on lying time. However, the effect of treatment on frequency of lying bouts and on mean lying bout duration varied by parity level. Incompletely milked cows in 2nd parity had a higher number of lying bouts (11.9 bouts / d vs. 9.2 bouts / d) and shorter mean lying bout duration (57.8 min / bout vs. 66.7 min) than control cows. In 3rd parity or more, the opposite happened. Therefore, our results suggest that an incomplete milking may be slightly problematic for 2nd parity cows and, possibly, slightly beneficial for older cows. Whether the differences observed resulted from a biologic process (discomfort due to the incomplete milking) or from random error will have to be determined by future research.